Characterizing the Parallel Simulation of P Systems on the GPU - Miguel A. Martínez-del-Amor; Jesús Pérez-Carrasco; Mario J. Pérez-Jiménez (Old City Publishing Inc., 2013)
In order to provide efficient software tools to handle large membrane systems, high-throughput simulators are required. Parallel computing platforms are good candidates, since they are capable of partially implementing the inherently parallel nature of the model. In this concern, today GPUs (Graphics Processing Unit) are considered as highly parallel processors, and they have been successfully used to accelerate P system simulators. A new GPU simulator for a quadratic-time solution to SAT by means of tissue P systems with cell division is presented in this paper. This simulator is compared with a previously introduced GPU-based simulator for a linear-time solution to SAT based on P systems with active membranes. The aim of this paper is to further study which ingredients of different P systems models are well suited to be managed by the GPU.
Keywords: GPGPU; Membrane computing; SAT; Tissue P Systems